Pengaruh Self-Efficacy terhadap Kinerja Akademik Mahasiswa di UIN Maulana Malik Ibrahim Malang - indi, rovida (Maliki Interdisciplinary Journal, 2025)
Self-efficacy plays a crucial role in shaping the academic performance of students. This study aims to explore the influence of self-efficacy on the academic performance of students at UIN Maulana Malik Ibrahim Malang, along with supporting and inhibiting factors. The method used is a literature review based on scientific works and theses by UIN Malang students that discuss self-efficacy, along with theoretical analysis. The findings show that students with high self-efficacy tend to have stronger motivation, use efficient learning strategies, and cope with academic pressure better. Social support, prior experience, and positive feedback from lecturers and the academic environment strengthen self-efficacy. Conversely, imposter syndrome, academic stress, and lack of social support can hinder its development. It is recommended that educational institutions implement self-efficacy development training and provide a supportive academic environment to improve students’ academic performance.